PEMODELAN DAN ESTIMASI POTENSI BATUBARA DI DAERAH JANGGA, KABUPATEN BATANG HARI, PROVINSI JAMBI: MODELING AND COAL POTENTIAL ESTIMATION IN JANGGA AREA, BATANG HARI REGENCY, JAMBI PROVINCE - Rizki Satria Rachman; Rino Destama Sugandhi; Rezky Aditiyo; Sigit Arso Wibisono (Buletin Sumber Daya Geologi, 2022)
Coal is one of the largest commodities used to produce electrical energy in Indonesia. As considered that coal is non-renewable energy, it is important to find new potential sources of coal. Exploration was carried out in the Jangga area, Batang Hari Regency, Jambi Province. It was an early stage exploration activity carried out by Center for Mineral, Coal dan Geothermal Resources, which consists of two activities, namely surface geological mapping and core drilling. After that, data processing was carried out to determine the 3D coal seam model and estimate the potential of coal. Two main rock units can be observed from geological mapping, namely sandstone and claystone units. Three coal outcrops were also found. Drilling activities were carried out at four locations, namely MK-01, MK-02, MK-03, and MK-04. Coal seam modeling and potential estimation were carried out using MineScape 5.7 software. From the results of the drilling data, there are 8 coal seams that can be modeled with supporting data in the form of coal outcrop data. The estimation of coal potential in this study refers to the exploration target group and the coal inventory group. From the estimation results, it is known that the minimum total exploration target is 1,158,822.74 tons and the maximum is 4,208,379.08 tons. Meanwhile, the total estimated coal potential in the inferred inventory group is 12,916,775.7 tons and the indicated inventory is 9,296,304.45 tons.